2021
DOI: 10.1111/jace.18087
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on micromechanical properties and biological performances in hydroxyapatite ceramics with micro/nanocrystalline

Abstract: Due to excellent biocompatibility, osteoconductivity and bioactivity, hydroxyapatite (HA) bioceramics have been widely used in the field of bone repairing. 1,2 Generally, HA bioceramics are limited in non-bearing bone filling due to their inherent brittleness and poor mechanical strength. [3][4][5] Up to now, the extensive efforts have been taken to enhance the mechanical strength of HA bioceramics. Some studies attempted to introduce second phase or fibers to improve the mechanical strength of HA bioceramics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Researchers have conducted a wide range of studies addressing this issue. Wu [ 15 ] found that nano-HA ceramics could decrease the hardness and fracture toughness of HA ceramics with an increase in crystallinity. First-principles and molecular dynamics simulations were used by Shang [ 16 ] to study HA’s crystal structure and adsorption capacity for macromolecular drugs; it was found that Zn-doping effectively improved the binding energy between doxorubicin (DOX) and HA.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have conducted a wide range of studies addressing this issue. Wu [ 15 ] found that nano-HA ceramics could decrease the hardness and fracture toughness of HA ceramics with an increase in crystallinity. First-principles and molecular dynamics simulations were used by Shang [ 16 ] to study HA’s crystal structure and adsorption capacity for macromolecular drugs; it was found that Zn-doping effectively improved the binding energy between doxorubicin (DOX) and HA.…”
Section: Introductionmentioning
confidence: 99%